FEATURES OF PREGNANCY AND DELIVERY IN WOMEN WITH DIFFERENT FORMS OF HYPERANDROGENISM - Семенюк Л. Н.; Ліхачов В. К.; Добровольська Л. Н.; Удовицька Н. О.; Макаров О. Г. (World of Medicine and Biology, 2015)
The peculiarities of gestation in 150 women with various forms of hyperandrogenism. There was a significantly higher incidence of threatened abortion, placental insufficiency, increased frequency of fetal distress during labor, which led to the frequency of operative delivery in this cohort of women compared with healthy patients. The most unfavorable outcome of pregnancy and childbirth was a group of women with mixed hyperandrogenism, which apparently caused a deep pathological processes arising pregravid on stage and manifest imbalances in the body of a pregnant gestational restructuring and complexities involved in their delivery. All of the above makes the search for new markers of early endocrine disbalance in the body of the expectant mother, to conduct timely prevention and correction established pathology first step gestational debut, thereby ensuring safe motherhood.
Keywords: hyperandrogenism; miscarriage; fetal malnutrition; fetal distress